IRAN-ISRAEL SALING SERANG HARGA MINYAK MENTAH MERANGKAK NAIK DAMPAKNYA TERHADAP EKONOMI RI - Karso, A. Junaedi (SINERGI : Jurnal Riset Ilmiah, 2025)
The shock of the conflict resurfaced after the Israeli military attacked Iran.  The Iranian government is considering closing the Strait of Hormuz. The strait is the main route for shipping oil to and from the Persian Gulf. "Saudi Arabia, Kuwait, Iraq and Iran are completely locked in one small lane for exports," he said. As a result of the Israeli-Iranian attack,  world crude oil prices  continue to rise after the escalation of the conflict in the Middle East; (1). Brent crude oil prices are estimated to increase to 75 US dollars per barrel, up 2 percent; (2). The price of Brent oil fell to 69 US dollars per barrel after which the price rose again, above 70 US dollars per barrel; (3). The attack opens up the possibility of disruption of oil supply to various countries. The impact of the Israeli-Iranian war on the global economy: (1). Oil prices rise-Global logistics are stuck; (2). Israeli Panic Buying; (3). Iran that has sent a counterattack has made the Israeli government panic.; (4). Russia can profit; (5). The price of Brent crude oil as a global benchmark jumped from US$ 69.36 to US$ 75 per barrel; (6). International Flight Delays; (7). A number of international airlines canceled flights to Israel and avoided Middle Eastern airspace.  Measuring the Impact  of the Iran-Israel Conflict on the Indonesian Economy from the Escalation of the Israeli-Iranian Conflict, namely: (1). Brent crude oil prices recorded an increase of 0.21 percent to 87.29 US dollars per barrel, while West Texas Intermediate (WTI) oil also increased by 0.5 percent to 83.14 US dollars per barrel; (2). For Indonesia, the rise in world oil prices means that the Government needs to rack its brains to hold the price of fuel oil (BBM) to remain affordable for the public. Indonesia's anticipation in overcoming the impact of the Iran-Israel conflict: (1). The government will not increase fuel prices until next June;  (2). The Iran-Israel conflict remains indirectly impacted because the attack between the two countries occurred near the Strait of Hormuz, which is one of the crucial logistics routes; (2). This conflict is likely to confront the Government of Indonesia with two dilemmas, namely between being forced to increase fuel prices or adjusting the fuel subsidy budget to contain price spikes.